Antiglycine receptor antibody related disease: a case series and literature review. (21st July 2018) - Swayne, A.; Tjoa, L.; Broadley, S.; Dionisio, S.; Gillis, D.; Jacobson, L.; Woodhall, M. R.; McNabb, A.; Schweitzer, D.; Tsang, B.; Vincent, A.; Irani, S. R.; et al.
Abstract : Background and purpose: Antibodies to glycine receptors (GlyR‐Abs) were first defined in progressive encephalopathy with rigidity and myoclonus (PERM) but were subsequently identified in other clinical presentations. Our aim was to assess the clinical associations of all patients identified with GlyR‐Abs in Queensland, Australia, between April 2014 and May 2017 and to compare these to cases reported in the literature. Methods: A literature review identified the clinical features of all published GlyR‐Ab‐positive cases through online databases. A case series was undertaken via collection of clinical information from all patients diagnosed or known to immunology, pathology or neurological services in Queensland during the study period of 3 years. Results: In all, 187 GlyR‐Ab‐positive cases were identified in the literature. The majority (47.6%) had PERM, 22.4% had epilepsy, but the remaining 30% included mixed phenotypes consisting of cerebellar ataxia, movement disorders, demyelination and encephalitis/cognitive dysfunction. By contrast, in our series of 14 cases, eight had clinical presentations consistent with seizures and epilepsy and only three cases had classical features of PERM. There was one case each of global fatiguable weakness with sustained clonus, laryngeal dystonia and movement disorder with hemiballismus and tics. The rate of response to immune therapy was similar in all groups. Conclusion: Antibodies to glycine receptors are linked to a spectrum of neurological disease. The results of the literature review and our case series suggest a greater relationship between GlyR‐Abs and epilepsy than previously reported.